From positive geometries to a coaction on hypergeometric functions - Britto, Ruth (My University, 2020)
It is well known that Feynman integrals in dimensional regularization often evaluate to functions of hypergeometric type. Inspired by a recent proposal for a coaction on one-loop Feynman integrals in dimensional regularization, we use intersection numbers and twisted homology theory to define a coaction on certain hypergeometric functions. The functions we consider admit an integral representation where both the integrand and the contour of integration are associated with positive geometries. As in dimensionally- regularized Feynman integrals, endpoint singularities are regularized by means of expo- nents controlled by a small parameter ε. We show that the coaction defined on this class of integral is consistent, upon expansion in ε, with the well-known coaction on multiple polylogarithms. We illustrate the validity of our construction by explicitly determining the coaction on various types of hypergeometric p+1Fp and Appell functions.
PUBLISHED
Keywords: Scattering Amplitudes; Perturbative QCD; Algebra; Theoretical Physics